KAJIAN BARU DALAM PEMBELAJARAN ANALISA SISTEM TENAGA BERBASISKAN PRACTICAL-COMPUTER BASED LEARNING - Ici Taufik Pulungan; Adi Sastra P Tarigan; Solly Aryza (Ensiklopedia Education Review, 2022)
Strengthening the competitiveness of human resources is the responsibility of higher education institutions as providers of higher formal education. UNPAB Electrical Engineering Study Program (TE UNPAB Study Program) as one of the study programs that manages the field of electrical engineering expertise has a very important role in preparing the human resources (HR) needed by the business world and industry. KKNI-based curriculum 2015. The 2015 TE UNPAB Study Program curriculum based on KKNI was prepared as a way to answer the challenges of global competitiveness, where graduates produced by UNPAB TE Study Programs are expected to be able to compete globally, especially related to the implementation of the Asean Economic Community (MEA) which requires active participation graduates with competence and competitive quality of human resources. The preparation for the formation of competitive human resources is carried out with various strategies contained in the Seven (7) Higher Education Standards, one part of which is the implementation of the teaching and learning process in the Electrical power system analysis course with short circuit analysis material (Short Circuit Calculation. This course is a subject core courses that form the basis for other competency courses in the advanced semester of the UNPAB TE Study Program The development of the Computer Based Learning (CBL) model is carried out in learning multi-machine short circuit analysis which includes: (a) Single-phase short circuit fault, (b) ) Two-Phase Short Circuit Fault, (c) Two Phase Earth Short Circuit Fault, (d) Single Phase Earth Short Circuit Fault The development of the CBL learning model for the Electrical Power System Analysis course provides space for students to be more active in learning in completing complex problems (complicated), so that produce flexibility in active student learning methods to solve short circuit analysis problems and form student active participation in learning (Student Center Learning) in the process of electric power system analysis lecture activities.Keywords: Active Learning CBL, Short Curcuit Calculation (SCC).